A review of the utility of high-frequency oscillatory ventilation in burn and trauma ICU patients. Issue 2 (22nd April 2023) - Dilday, Joshua; Leon, David; Kuza, Catherine M.
Abstract : Purpose of review: The purpose was to examine the utility of high-frequency oscillatory ventilation (HFOV) in trauma and burn ICU patients who require mechanical ventilation, and provide recommendations on its use. Recent findings: HFOV may be beneficial in burn patients with smoke inhalation injury with or without acute lung injury/acute respiratory distress syndrome (ARDS), as it improves oxygenation and minimizes ventilator-induced lung injury. It also may have a role in improving oxygenation in trauma patients with blast lung injury, pulmonary contusions, pneumothorax with massive air leak, and ARDS; however, the mortality benefit is unknown. Summary: Although some studies have shown promise and improved outcomes associated with HFOV, we recommend its use as a rescue modality for patients who have failed conventional ventilation.